2018
DOI: 10.21608/ejabf.2018.22061
|View full text |Cite
|
Sign up to set email alerts
|

Stock assessment and management of the rabbitfish Siganus rivulatus from the Southern Red Sea, Egypt

Abstract: Rabbitfishes, family Siganidae, are one of the most abundant fishes inhabiting the Red Sea and now widely distributed in the Mediterranean. Age and growth of Siganus rivulatus, the most common species, were studied from samples collected randomly between October 2017 and October 2018 from Shalatein landing site. Otoliths of 2000 specimens were used for age determination and the maximum attained age for this species was four years. The von Bertalanffy growth parameters L ∞ , K and t o and the instantaneous annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Conversely, 20.0 cm TL was declared to be the length of first sexual maturation from the southern Red Sea, Egypt by Mehanna et al . (2018). Differences between the previous studies about the length at maturity are relatively small and discrepancies may be attributed to sampling techniques, geographic disparity and the sampling year of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, 20.0 cm TL was declared to be the length of first sexual maturation from the southern Red Sea, Egypt by Mehanna et al . (2018). Differences between the previous studies about the length at maturity are relatively small and discrepancies may be attributed to sampling techniques, geographic disparity and the sampling year of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The overfishing situation was observed (Table 4) and agreed with all previous studies dealing with tstock assessment of Red Sea fisheries (eg. Mehanna and El-Gammal, 2007;Mehanna, 2005Mehanna, to 2020Tesfamichael and Mehanna, 2012;Osman, 2015;Mohamed, 2016;El-Mahdy, 2017;Mehanna et al, 2016Mehanna et al, , 2017Mehanna et al, , 2018Mehanna et al, , 2019Mohamed et al, 2020). In spite of the large area of marine fisheries in Egypt, these fisheries are not exploited rationally due to the decrease of relative abundance of its fish stocks as a result of different reasons such as pollution (domestic and industrial sewages), over fishing and illegal fishing, habitat degradation, human activities on coastal areas, in addition to climate changes.…”
Section: Msy and F Max For Red Sea Fisheriesmentioning
confidence: 99%
“…The analysis of length-frequency data can be used for the estimation of age, growth, survival, mortality rates and analytical yield models such as the yield per recruit (Beverton and Holt, 1966;Gulland ,1971;Pauly, 1984;Mehanna et al, 2018). It was found that, there is a great variability in length distribution pattern of the two grouper species.…”
Section: Length Frequency Distributionmentioning
confidence: 99%